Global DNA methylation and hydroxymethylation differ in hepatocellular carcinoma and cholangiocarcinoma and relate to survival rate. Issue 2 (28th April 2015) - Udali, Silvia; Guarini, Patrizia; Moruzzi, Sara; Ruzzenente, Andrea; Tammen, Stephanie A.; Guglielmi, Alfredo; Conci, Simone; Pattini, Patrizia; Olivieri, Oliviero; Corrocher, Roberto; Choi, Sang‐Woon; Friso, Simonetta
<x xml:space="preserve">Abstract</x> In addition to DNA methylation, hydroxymethylation of DNA is recognized as a novel epigenetic mark. Primary liver cancers, i.e., hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC), are highly prevalent but epigenetically poorly characterized, so far. In the present study we measured global methylcytosine (mCyt) and hydroxymethylcytosine (hmCyt) in HCC and CC tissues and in peripheral blood mononuclear cell (PBMC) DNA to define mCyt and hmCyt status and, accordingly, the survival rate. Both mCyt and hmCyt were measured by a liquid chromatography/tandem mass spectrometry method in neoplastic and homologous nonneoplastic tissues, i.e., liver and gallbladder, and in PBMCs of 31 HCC and 16 CC patients. Content of mCyt was notably lower in HCC than in CC tissues (3.97% versus 5.26%, respectively; P < 0.0001). Significantly reduced mCyt was also detected in HCC compared to nonneoplastic tissue (3.97% versus 4.82% mCyt, respectively; P < 0.0001), but no such difference was found for CC versus homologous nonneoplastic tissue. Hydroxymethylation was significantly decreased in HCC versus nonneoplastic liver tissue (0.044 versus 0.128, respectively; P < 0.0001) and in CC versus both liver and gallbladder nonneoplastic tissue (0.030 versus 0.124, P = 0.026, and 0.030 versus 0.123, P = 0.006, respectively). When the survival rate was evaluated according to mCyt PBMC content by Kaplan‐Meier analysis, patients with mCyt ≥5.59% had a significantly higher life expectancy than those with mCyt <5.59% (P = 0.034) at a follow‐up period up to 48 months. Conclusion: A significant DNA hypomethylation distinguishes HCC from CC, while DNA hypo‐hydroxymethylation characterizes both HCC and CC, and a PBMC DNA mCyt content ≥5.59% relates to a favorable outcome in primary liver cancers. (Hepatology 2015;62:496–504